Characteristics of Pediatric Emergency and Risk Factors for Life-saving Interventions - Phatthranit Phattharapornjaroen MD; Yuwares Sittichanbuncha MD; Pongsakorn Atiksawedparit MD, PhD; Kittisak Sawanyawisuth MD, PhD (SAGE Publishing, 2021)
Pediatric emergency patients are vulnerable population and require special care or interventions. Nevertheless, there is limited data on the prevalence and risk factors for life-saving interventions. This study is a retrospective analytical study. The inclusion criteria were children aged 15 years or under who were triaged as level 1 or 2 and treated at the resuscitation room. Factors associated with LSI were executed by logistic regression analysis. During the study period, there were 22 759 ER visits by 14 066 pediatric patients. Of those, 346 patients (2.46%) met the study criteria. Triage level 1 accounted for 16.18% (56 patients) with 29 patients (8.38%) with LSI. Trauma was an independent factor for LSI with adjusted odds ratio (95% CI) of 4.37 (1.49, 12.76). In conclusion, approximately 8.38% of these patients required LSI. Trauma cause was an independent predictor for LSI.